TRANSFORMASI STRATEGI PEMBENTUKAN MURID SEBAGAI KATALISATOR PEKABARAN INJIL DI RUANG SIBER - Perangin Angin, Yakub Hendrawan; Yeniretnowati, Tri Astuti (The Way: Jurnal Teologi dan Kependidikan, 2026)
This article examines the persistent reality that churches and individual Christians have not yet positioned discipleship as the primary orientation in fulfilling the Great Commission of Jesus Christ. Instead, many churches and believers remain preoccupied with physical buildings and service-oriented activities in their stewardship, thereby neglecting the central mandate of disciple-making. Employing a library research method and thematic analysis, this study explores the relationship between disciple formation and evangelism within the framework of transformative discipleship as a catalyst for Gospel proclamation. The findings demonstrate that when churches and individual believers simultaneously are encouraged to become catalysts for evangelism in cyberspace in a rapid and sustainable manner, thereby fulfilling the Great Commission of Jesus Christ.